"Gender" and "innovation" in facility management: do they matter?. Issue 2 (8th March 2020) - Staffansson Pauli, Karin; Kristoferson, Caroline Wigren; Stevenson, Anna
Abstract : Purpose: The purpose of this paper is to contribute to the ongoing discussion on how the field of facility management is changing and the role a regional innovation system (RIS) can take place to support this change, with a specific focus on the role of gender and innovation. Design/methodology/approach: The study builds partly on interactive research, and as a complement, qualitative semi-structured telephone interviews have been conducted. Findings: The role of gender and innovations in facility management does matter due to the fact that if aiming at creating innovations, it is necessary to break free from established institutions, both formal and informal. Working with gender demands a norm-critical approach, and to be critical towards what we take for granted might create new solutions. Research limitations/implications: The study is conducted in a Swedish context. Practical implications: This paper brings gender issues in facility management to the forefront in an effort to engage the industry. Originality/value: The paper contributes to the ongoing discussions how the field of facility management is changing and the importance of including gender in the innovation discussions.